ANALISIS PROGRAM KEMITRAAN DAN BINA LINGKUNGAN (PKBL) PTPN VII DI PROPINSI LAMPUNG - Handy Nugroho (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2015)
This study aims to identify and analyze the partnership program thad already implementedby PTP Nusantra VII (Persero) into their Small Medium Enterprise (SME) partner or “mitra binaan”had an increased growth. This increase on growth measured from the increase in business profits,number of employees, sales and production of goods and loans that have been granted to thepartners.Results of a survey conducted found that Partnership program run by PTPN VII has raisedprofit venture established partners in the third sector, trade, industry, and agriculture. Only fewpartner had a problem in loans return, mainly in palm oil plantation partnership.